Assessing the Health Economic Outcomes from Commercially Insured Relapsing Multiple Sclerosis Patients Who Switched from Other Disease-Modifying Therapies to Teriflunomide, in the United States - Araujo L; Kyatham S; Bzdek KG; Higuchi K; Greene N (Dove Medical Press, 2023)
Lita Araujo,1 Srikanth Kyatham,2 Kristen G Bzdek,1 Keiko Higuchi,1 Nupur Greene1 1Neurology and Immunology, Sanofi, Cambridge, MA, USA; 2Axtria Inc, Berkeley Heights, NJ, USACorrespondence: Lita Araujo, Neurology and Immunology, Sanofi, 450 Water Street, Cambridge, MA, 02141, USA, Tel +1 617 937 9928, Email Lita.Araujo@sanofi.comObjective: Assess patient characteristics, healthcare resource utilization (HCRU), and relapses in patients with multiple sclerosis (MS) who switched to teriflunomide from other disease-modifying therapies (DMTs).Methods: Retrospective study of US Merative™ MarketScan® claims database (Jan 1, 2012-July 31, 2020,) including HIPAA-compliant, deidentified data. Patients ≥ 18 years with MS diagnosis (based on ICD-9/ICD-10 codes), receiving ≥ 1 DMT prior to teriflunomide and ≥ 12 months continuous enrollment pre and post index (date of teriflunomide initiation). Outcomes included inpatient and emergency room claims coinciding with MS diagnosis, MS-related healthcare costs, and annualized relapse rates (ARRs) (indirectly assessed using hospitalization/outpatient claims and steroid use coinciding with MS diagnosis).Results: The analyzed cohort (N=2016) was primarily female (79%); age (mean ± standard deviation) 51.4 ± 9.3 years; MS duration 4.7± 2.8 years (at index). The majority (89.2%) were treated with one DMT before switching to teriflunomide. Use of outpatient services (event rate/100 person-years) increased post vs pre index; however, MRI visits significantly reduced over the same period (both P< 0.0001). Costs for MS-specific outpatient visits decreased by $371 per patient per year (PPPY) after switching to teriflunomide. Despite an increase in use post index (0.024 to 0.033 rate/100 person-years; P< 0.0001), costs for MS-specific laboratory services reduced (pre-index: $271 vs $248 PPPY post-index; P=0.02). Fewer patients had relapses after switching (pre-index: n=417 [20.7%]; post-index: n=333 [16.5%]). ARR was significantly lower after switching (pre-index: 0.269 vs post-index: 0.205; P=0.000).Conclusion: Switching to teriflunomide from existing DMTs in patients with relapsing MS resulted in a reduction in outpatient HCRU in this analysis of US claims data. The real-world effectiveness of teriflunomide was generally consistent with efficacy reported in clinical trials, showing a reduction in relapse following a switch to teriflunomide.Keywords: DMTs, healthcare resource utilization, healthcare costs, prescription, relapsing-remitting multiple sclerosis